Narratives of reconstruction: Looking beyond biographical disruption through three Indian breast cancer memoirs - Bhattacharyya M.; Mishra A.K. (My University, 2025)
Despite extensive research on Western breast cancer (BC) memoirs highlighting how shame profoundly impacts patients’ lives making them more vulnerable, Indian BC memoirs remain underexplored, especially in understanding the challenges of shame. This article examines the unique struggles of Indian female BC patients, focusing on their experiences of biographical disruption, the guilt-ridden consciousness of their altered body image, and the shame-induced actions that shape their narratives. Through an analysis of three Indian BC memoirs, Sunshine (2011), To Cancer, with Love (2015) and Cancer, You Picked the Wrong Girl (2021), this article explores how Indian female BC narrators comprehend and articulate their lived experiences of shame and self-perception. The analysis also highlights the diverse coping strategies such as doing humour, normalising breast talk, practising spirituality, and sharing survival lessons employed by these narrators to offer a deeper understanding of the intersection of shame, identity, and healing, and to transcend moments of shame through acts of reconstruction. More importantly, the analysis underscores how these acts of reconstruction provide empowering strategies for navigating the challenges of BC and accentuate the possibility of an autobiographical reconstruction mechanism. © The Author(s) 2025.